Medication error reporting in Ghana: A multicenter assessment of healthcare professionals’ knowledge, attitudes and practices - Stephen Mensah Arhin; Isaac Tabiri Henneh; Kwasi Sobre Nkrumah; Ewura Seidu Yahaya; Phyllis Elsie Owusu Agyei; Meshack Antwi-Adjei; Martins Ekor (PLoS ONE, 2026)
Background Medication errors (MEs) remain a leading cause of preventable patient harm globally, with significant implications in low- and middle-income countries (LMICs) where reporting systems are not standardized. Understanding healthcare professionals’ knowledge, attitudes and practices is critical to designing interventions that strengthen patient safety. Methods A cross-sectional, multicenter study was conducted among healthcare professionals, including nurses, doctors, and pharmacists. A structured questionnaire assessed sociodemographic characteristics, knowledge of categories and sources of MEs, medication administration practices, and awareness and use of error reporting systems. Data were analyzed using descriptive statistics and Poisson regression with robust standard errors to identify factors associated with reporting system awareness. Results A total of 2078 healthcare professionals including nurses, doctors, and pharmacists were surveyed. Knowledge levels varied across different medication error categories, with highest recognition for wrong dose (85.5%) and wrong patient errors (81.5%), while shortage of drugs showed lower recognition (44.0%). While adherence to some safety practices was strong (86.6% always checked patient identity), unsafe behaviors such as preparing medications for more than one patient at a time (37.4%) and failure to double-check insulin doses (only 33.9% compliance) were reported. Although 62.6% were aware of institutional error reporting systems, only 23.6% consistently reported errors, and over 53% were uncertain about the process of submitting incident forms. Conclusion Healthcare professionals in Ghana demonstrate strong knowledge of medication error categories and sources but notable gaps persist in safe medication practices and reporting behaviors. Despite moderate awareness of reporting systems, utilization remains poor, reflecting systemic and cultural barriers. These findings highlight the need for targeted educational interventions and system improvements to enhance medication safety culture and error reporting practices across different healthcare specialties and experience levels.